2023
DOI: 10.1039/d3nr00507k
|View full text |Cite
|
Sign up to set email alerts
|

A curtain purification system based on a rabbit fur-based rotating triboelectric nanogenerator for efficient photocatalytic degradation of volatile organic compounds

Abstract: Efficient removal of air pollution caused by volatile organic compounds (VOCs) and particulate matter (PM) through distributed energy collected from the environment is an effective strategy to achieve both energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, scientists are looking into different solutions to preserve materials, like segmenting triboelectric layers, using rabbit fur in between triboelectric layers and electrodes, etc. [78,79]…”
Section: Wave and Ocean Current Energy Harvestersmentioning
confidence: 99%
“…However, scientists are looking into different solutions to preserve materials, like segmenting triboelectric layers, using rabbit fur in between triboelectric layers and electrodes, etc. [78,79]…”
Section: Wave and Ocean Current Energy Harvestersmentioning
confidence: 99%
“…It can be observed that solid–solid CE, which has been studied the longest and has the best underlying theory, also has the most application scenarios. However, other states of matter have their own strengths, such as the unique application of solid–liquid CE in catalysis [ 140 ], and interfaces containing gases have a unique advantage in air purification [ 157 ].…”
Section: Highlighting Unique Applications Of Contact Electrification ...mentioning
confidence: 99%
“…Volatile organic compounds (VOCs), which are primary constituents of atmospheric pollution, have the potential to interact with breathed air via processes such as evaporation or sublimation, hence posing risks to both the ecological environment and human health. , Hence, a significant area of focus in current research pertains to the development of effective detection methods and removal technologies for VOCs that pose environmental risks. These VOCs include xylene (C 8 H 10 ), acetone (CH 3 COCH 3 ), formic acid (HCOOH), acetic acid (CH 3 COOH), and formaldehyde (HCHO), as highlighted in previous studies. , Among these deleterious VOCs, formic acid is acknowledged as a significant VOC with detrimental effects. It possesses a diverse array of practical uses, such as serving as a preserving or antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%
“…These VOCs include xylene (C 8 H 10 ), acetone (CH 3 COCH 3 ), formic acid (HCOOH), acetic acid (CH 3 COOH), and formaldehyde (HCHO), as highlighted in previous studies. 3 , 4 Among these deleterious VOCs, formic acid is acknowledged as a significant VOC with detrimental effects. It possesses a diverse array of practical uses, such as serving as a preserving or antimicrobial agent.…”
Section: Introductionmentioning
confidence: 99%